Fibre optic pressure sensor and monitoring of structural defects - Pandey, N.K.; Yadav, B.C. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Pressure induced microbends have been created in a 50 mm graded index multimode optical fibre with spatial periodicity L = 4.5 mm, embedded in the sample of araldite. If high pressure is applied directly to optical fibre having microbends, it may break, and if pressure is applied to embedded fibre in a solid structure without microbends, the sensitivity is lower. In this paper, a combination of the embedded sensor and microbend sensor is presented. It has the advantage of sensing high pressure on a structure with the sensitivity of a microbend sensor without breaking the optical fibre. It measures pressure up to 1.6 MPa with reproducibility within ± 5% of the measurand. The average sensitivity of the sensor is 5.3/ MPa on an arbitrary scale.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 57-63
Keywords: optyka; fibre; pressure sensor; microbend; structural defects